Efficacy of bevacizumab combined with chemotherapy in the treatment of HER2-negative metastatic breast cancer: a network meta-analysis - Zhengwu Sun (BMC Cancer, 2020)
Abstract Background It is not known what combination of bevacizumab and chemotherapy agents is the best therapeutic regimen. Comparative study results among the efficacies of bevacizumab plus chemotherapy remain controversial in patients with HER2-negative metastatic breast cancer. Methods We searched Pubmed, Embase, and Cochrane Library Central Resister of Controlled Trials through were July 2019 for randomized controlled trials that evaluated the efficacy of bevacizumab plus chemotherapy in HER2-negative metastatic breast cancer. Data on included study characteristics, outcomes, and risk of bias were abstracted by two reviewers. Results A total of 16 RCT studies involving 5689 patients were included. The results showed that bevacizumab (Bev) - taxanes (Tax) - capecitabine (Cap) has highest-ranking and is probably more effective for prolonging progression-free survival (PFS) than Tax, Cap, Bev-Tax and Bev-Cap, which was no convincing differences among Bev-Cap-vinorelbine, Bev-Tax-everolimus, Bev-Tax-trebananib, Bev-exemestane, Bev-Cap-cyclophosphamide in Bev-containing regimens. For overall response rate (ORR), Bev-Tax-Cap is superior to Tax, Cap and Bev-Cap, while Bev-Tax-trebananib is superior to Cap. The cumulative probability ranking showed that Bev-Tax-Cap or Bev-Tax-trebananib may have best pathological response rate in HER2-negative metastatic breast cancer. Conclusion Our results provide moderate quality evidence that bevacizumab-taxanes-capecitabine maybe the most effective bevacizumab plus chemotherapy on PFS and ORR in HER2-negative metastatic breast cancer, however it should be also considered that bevacizumab may add toxicity to chemotherapy and whether improve overall survival (OS) or not.